The Influence of Digital Public Engagement on Public Trust through Public Satisfaction with Public Services - Susi Sugiyarsih (International Journal of Science Education and Cultural Studies, 2026)
The rapid growth of digital public services has changed the way citizens interact with government institutions and digital public engagement has become a more and more important factor in shaping public perceptions of government performance. Even though investments in digital governance are growing, the mechanisms by which digital public engagement contributes to public trust are not well understood. This study explores the effect of Digital Public Engagement on Public Trust and the mediating effect of Public Satisfaction in this relationship. This research uses a quantitative method with data taken from a survey of 180 citizens of Cirebon City who had used digital public services in the last three months. Data were analyzed using PROCESS Macro Model 4 (regression-based mediation analysis. The results show that Digital Public Engagement has a positive and statistically significant impact on Public Satisfaction and Public Trust. Public Satisfaction has a positive effect on the Public Trust and a mediating effect between Digital Public Engagement and Public Trust partially. These findings suggest that citizens’ trust in government institutions is not only shaped by their satisfaction with digital public services but also by their direct experiences of accessibility, responsiveness and interaction through government digital platforms. The research contributes to the digital governance literature by revealing the dual effect of digital public engagement on public trust. The findings also underscore the need to improve digital engagement strategies to enhance citizen satisfaction and institutional trust in the delivery of public services.